Rancang Bangun Untuk Kontruksi Dinding Rumah dengan Bahan Bata Interlok - Hayati, Yulia; Sabri; Aprilia, Cut; Malahayati, Nurul; Asyifa, Cut Nella; Munirwansyah; Afifuddin, Mochammad (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
The type of material, mixture composition, and production process are among the factors that influence the strength of interlock bricks. In this study, interlocking bricks are used for the construction of residential wall structures. The interlocking brick mixture consists of cement, fly ash, sand, and water. The fly ash and sand used have a maximum diameter of 4.75 mm and are not subjected to calcination. Interlocking bricks measuring 30 cm x 20 cm x 10 cm are molded using a manual hydraulic press and cured for up to 28 days before being cut into test specimens measuring 5 cm x 5 cm x 5 cm. A total of 150 test specimens from 5 mix designs using water-cement ratios (WCR) of 0.3, 0.4, and 0.5 were utilized in this study. The objective of this research is to determine the quality levels of interlocking bricks based on compressive strength tests at 28 days of age. The quality levels are determined according to the Indonesian National Standard, SNI 03-0349-1989. Based on the compressive strength results, it was found that the average interlocking bricks with fly ash mixture achieved class III quality, indicating that they can only be used for non-structural wall applications.